CARBON-RICH CHONDRITIC CLAST PV1 FROM THE PLAINVIEW H-CHONDRITE REGOLITH BRECCIA: FORMATION FROM H3 CHONDRITE MATERIAL BY POSSIBLE COMETARY IMPACT - Rubin A.E.; Trigo-Rodriguez J.M.; Kunihiro T.; Kallemeyn G.W.; Wasson J.T. (My University, 2005)
Chondritic clast PV1 from the Plainview H-chondrite regolith breccia is a subrounded, 5-mm-diameter unequilibrated chondritic fragment that contains 13 wt% C occurring mainly within irregularly shaped 30–400-μm-size opaque patches. The clast formed from H3 chondrite material as indicated by the mean apparent chondrule diameter (310 μm vs. ∼300 μm in H3 chondrites), the mean Mg-normalized refractory lithophile abundance ratio (1.00 ± 0.09×H), the previously determined O-isotopic composition (Δ17O = 0.66‰ vs. 0.68 ± 0.04‰ in H3 chondrites and 0.73 ± 0.09‰ in H4-6 chondrites), the heterogeneous olivine compositions in grain cores (with a minimum range of Fa1-19), and the presence of glass in some chondrules. Although the clast lacks the fine-grained, ferroan silicate matrix material present in type 3 ordinary chondrites, PV1 contains objects that appear to be recrystallized clumps of matrix material. Similarly, the apparent dearth of radial pyroxene and cryptocrystalline chondrules in PV1 is accounted for by the presence of some recrystallized fragments of these chondrule textural types. All of the chondrules in PV1 are interfused indicating that temperatures must have briefly reached ∼1100°C (the approximate solidus temperature of H-chondrite silicate). The most likely source of this heating was by an impact. Some metal was lost during impact heating as indicated by the moderately low abundance of metallic Fe-Ni in PV1 (∼14 wt%) compared to that in mean H chondrites (∼18 wt%). The carbon enrichment of the clast may have resulted from a second impact event, one involving a cometary projectile, possibly a Jupiter-family comet. As the clast cooled, it experienced hydrothermal alteration at low water/rock ratios as evidenced by the thick rims of ferroan olivine around low-FeO olivine cores. The C-rich chondritic clast was later incorporated into the H-chondrite parent-body regolith and extensively fractured and faulted.